Do Democratisation and Global Justice go hand in hand? The case of Timor-Leste - Luís, Carla (2013)
Peace missions often focus on statebuilding policies, being statebuilding a key aspect in these interventions. However, beyond or parallel to the democratisation process, questions regarding global justice arise. In this paper we are going to analyse the situation in Timor-Leste. We are going to argue that, beyond the classic democratisation approach, there are a number of factors that still have to be addressed, and these can be intrinsically related to democracy. We will conclude that the focus of the international interventions, especially within multi-dimensional missions and, therefore, the priorities of the host state, should go beyond the formal democratisation aspect. Social and economic factors, much related to the idea of global justice, should also be present and be a key aspect and result of these interventions.